2012
DOI: 10.1116/1.4751276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polarity and surface treatment on Ga- and N-polar bulk GaN

Abstract: The effects of polarity and surface treatment on the morphological, electrical, and optical behaviors in bulk GaN have been investigated. Kelvin probe, atomic force microscopy (AFM), and photoluminescence (PL) techniques were utilized to examine a set of freestanding, bulk GaN samples, which were grown by halide vapor phase epitaxy. The Ga- and N-polar surfaces were treated with either a mechanical polish (MP) or chemical mechanical polish (CMP), which influences the morphology, surface photovoltage (SPV), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…The fast initial SPV decrease, i.e., an upwards band bending, for the as grown samples is caused by two fast processes . First, photogenerated holes further accumulate near the surface . The electron–hole‐pair generation by sub band gap illumination is possible inside the strong electric field due to the Franz–Keldish‐effect .…”
Section: Resultsmentioning
confidence: 99%
“…The fast initial SPV decrease, i.e., an upwards band bending, for the as grown samples is caused by two fast processes . First, photogenerated holes further accumulate near the surface . The electron–hole‐pair generation by sub band gap illumination is possible inside the strong electric field due to the Franz–Keldish‐effect .…”
Section: Resultsmentioning
confidence: 99%
“…1(b, right diagram). 20,29,30,35 In this process, physisorbed oxygen species become chemisorbed by receiving electrons from the bulk. In the case of band-to-band excitation, the electrons can overcome the reduced nearsurface barrier.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Various studies reported about these processes on GaN layers. 29,30 For example, Foussekis et al investigated the fast and slow SPV responses in different gas environments using a single wavelength for both doped and undoped GaN layers. The SPV changes and, thus, the band bending under continuous illumination are explained by photo-induced adsorption of surface species in air ambient and photo-induced desorption in vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…Because N-polar (Al,Ga)N is known to be easily oxidized 19,20 , with the effect stronger than on the Ga-polar surface, the need for surface protection is even more crucial in order to ensure a stable operation irrespectively of the environment conditions. Examining N-polar GaN/AlGaN structures with an in-situ MOCVD Si 3 N 4 a barrier height of ~ 1 eV at the Si 3 N 4 /GaN interface was determined via capacitance-voltage (C-V) measurements 21 .…”
Section: Contactless Electroreflectance Studies Coupled With Numericamentioning
confidence: 99%